2018
DOI: 10.1111/srt.12466
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for evaluating heel xerosis grade and the effects of moisturizer on heel skin dryness

Abstract: Our new methods of visually classifying heel dryness and quantifying dead skin cells using magnified images effectively evaluated heel skin properties. As heel skin is prone to dryness, daily repetitive application of moisturizer might be helpful for hydrating dry heel skin, and ultimately preventing complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Increased TEWL leads to activation of serine proteases such as SC chymotryptic enzymes by increasing the pH on the skin surface [17]. Increased TEWL is also correlated with xerosis [18]. In the present study, senile pruritus patients had higher TEWL values than control subjects, and TEWL value was positively correlated with pruritus severity score (data not shown).…”
Section: Discussionmentioning
confidence: 43%
“…Increased TEWL leads to activation of serine proteases such as SC chymotryptic enzymes by increasing the pH on the skin surface [17]. Increased TEWL is also correlated with xerosis [18]. In the present study, senile pruritus patients had higher TEWL values than control subjects, and TEWL value was positively correlated with pruritus severity score (data not shown).…”
Section: Discussionmentioning
confidence: 43%
“…TEWL leads to activation of serine proteases such as SC chymotryptic enzyme by increasing the pH on the skin surface (15). TEWL is also correlated to xerosis (16). In the current study, we found that the senile pruritus has a higher value of TEWL compared to that in controls, and the value of TEWL is positively correlated to the score of pruritus severity (data not shown).…”
Section: Correlation Of Ssl Alteration and Itch Severity In The Idiopmentioning
confidence: 41%
“…The skin trans epidermal water loss (TEWL) value and moisture content can be used as physiological indicators to re ect the skin barrier function. Previous studies reported that the increased TEWL and decreased hydration content were associated with skin xerosis [12]. Skin surface lipids (SSLs) are a mixture of sebaceous gland lipids and intercellular lipids located in the outer layer of epidermal cells [13].…”
Section: Introductionmentioning
confidence: 99%